Identification and Molecular Analysis of Putative Self-Incompatibility Ribonuclease Alleles in an Extreme Polyploid Species, Prunus laurocerasus L. - Halász, Júlia; Molnár, Anna Borbála; Ilhan, Gulce; Ercisli, Sezai; Hegedűs, Attila (Frontiers in Plant Science, 2021)
Cherry laurel (Prunus laurocerasus L.) is an extreme polyploid (2n=22x) species of the Rosaceae family where gametophytic self-incompatibility (GSI) prevents inbreeding. This study was carried out to identify the S-ribonuclease alleles (S-RNases) of P. laurocerasus using PCR amplification of the first and second intron region of the S-RNase gene, cloning and sequencing. A total of 23 putative S-RNase alleles (S1-S20, S5m, S13m, and S18m) were sequenced from the second (C2) to the fifth conserved region (C5), and they shared significant homology to other Prunus S-RNases. The length of the sequenced amplicons ranged from 505 to 1544 bp, and similar sizes prevented the proper discrimination of some alleles based on PCR analysis. We have found three putatively non-functional alleles (S5m, S18m and S9) coding for truncated proteins. Although firm conclusions cannot be drawn, our data seem to support that heteroallelic pollen cannot induce self-compatibility in this polyploid Prunus species. The identities in the deduced amino acid sequences between the P. laurocerasus and other Prunus S-RNases ranged between 44 and 100%, without a discontinuity gap separating the identity percentages of trans-specific and more distantly related alleles. The phylogenetic position, the identities in nucleotide sequences of the second intron and in deduced amino acid sequences found one or more trans-specific alleles for all but S10, S14, S18 and S20 cherry laurel RNases. The analysis of mutational frequencies in trans-specific allele pairs indicated the region RC4-C5 accepts the most amino acid replacements and hence it may contribute to allele-specificity. Our results form the basis of future studies to confirm the existence and function of the GSI system in this extreme polyploid species and the alleles identified will be also useful for phylogenetic studies of Prunus S-RNases as the number of S-RNase sequences was limited in the Racemose group of Prunus (where P. laurocerasus belongs to).